Wheat varietal identification study using common quality and disease PCR markers - Mandakh, Ariungerel; Baasansuren, Otgonbayar; Munkhbat, Tungalag; Yadamsuren, Myagmarsuren (Mongolian Journal of Agricultural Sciences, 2020)
The main vital cereal crop in Mongolia is wheat (Triticum spp .). There are more than 10000 wheat varieties are released and registered in the world wheat atlas up to the date. Internationally, wheat varieties are identified by their genotypes. However, local wheat varieties are being identified only by its phenotypic traits in Mongolia. Not significant study was carried out on wheat varietal identification. In this study, we aim to differentiate widely planting 6 local wheat varieties Darkhan-34, Darkhan-131, Darkhan-144, Darkhan-166, Tsogt and Khalkh-gol-1 using PCR based common quality and disease 22 markers. As a result, 10 out of 22 markers were detected in all wheat varieties in distinct sizes, 8 markers detected otherwise and 4 markers was not detected at all. Thus, the ZSBy9 marker which is specific marker to distinguish Darkhan-144, ZSBy8 primer which is specific marker to distinguish Khalkh gol-1, GluA1c and GluB1 Bx642 markers those are specific markers to distinguish Tsogt variety from other studied varieties respectively.